Above‐belowground linkages of functionally dissimilar plant communities and soil properties in a grassland experiment. Issue 9 (25th September 2020) - Steinauer, Katja; Heinen, Robin; Hannula, S. Emilia; De Long, Jonathan R.; Huberty, Martine; Jongen, Renske; Wang, Minggang; Bezemer, T. Martijn
Abstract: Changes in plant community composition can have long‐lasting consequences for ecosystem functioning. However, how the duration of plant growth of functionally distinct grassland plant communities influences abiotic and biotic soil properties and thus ecosystem functions is poorly known. In a field experiment, we established identical experimental subplots in two successive years comprising of fast‐ or slow‐growing grass and forb community mixtures with different forb:grass ratios. After one and two years of plant growth, we measured above‐ and belowground biomass, soil abiotic characteristics (pH, organic matter, soil nutrients), soil microbial properties (respiration, biomass, community composition), and nematode abundance. Fast‐ and slow‐growing plant communities did not differ in above‐ and belowground biomass. However, fast‐ and slow‐growing plant communities created distinct soil bacterial communities, whereas soil fungal communities differed most in 100% forb communities compared to other forb:grass ratio mixtures. Moreover, soil nitrate availability was higher after two years of plant growth, whereas the opposite was true for soil ammonium concentrations. Furthermore, total nematodes and especially bacterial‐feeding nematodes were more abundant after two years of plant growth. Our results show that plant community composition is a driving factor in soil microbial community assembly and that the duration of plant growth plays a crucial role in the establishment of plant community and functional group composition effects on abiotic and biotic soil ecosystem functioning under natural field conditions.